Attributes of the earthquake-uplifted intertidal habitats and their implications to the Maribojoc and Loon coastal fisheries - Rollon, Rene N. (Animo Repository, 2015)
Other than the devastating impact on infrastructures and human lives, the 7.2Mw earthquake that shook Bohol and its vicinity in October 2013 also apparently caused massive damage on the coastal habitats: (1) collapse of many coral reefs/domes compromised by underwater cracks, mostly>1m wide, traversing the numerous reef formations; (2) substantial ground subsidence (i.e., >1m in Tubigon and vicinity) with sea-level-rise implications to the existing mangroves and seagrass beds, and, (3) massive loss of intertidal habitats due significant ground uplift, drying up extensive areas of mangroves, seagrass beds, sandflats, and rocky shores particularly in the municipalities of Maribojoc and Loon. This paper provides quantification of the attributes of the uplifted area, determining the pre-quake extent of the intertidal habitats, and attempting to reconstruct some intertidal community assemblages based on post-quake artefacts. We determined the total extent of the intertidal area severely affected by the ground uplift amounting to >400ha, comprised of mangroves (42 ha; 10%), seagrass beds (135 ha; 32%), reef slope corals (148; 35%), and intertidal sandflats, mudflats and rocky habitats (altogether, 94 ha; 22%). This impact may be grossly translated to a US$ 4.4 million of economic loss annually. Our ground elevation- and transect truthing surveys of habitat artefacts generally validated our areal approximations. Also, across these transects, we confirmed speciose pre-quake assemblage of important invertebrates and other taxa occurring in these intertidal areas. In strong contrast to the exposed seagrass beds and coral areas, which were already all dried-up and died, most mangroves were still surviving after 8 months post uplift (i.e., practically no more tidal inundation since Oct 2013), albeit now in strong competition against the aggressive colonization of terrestrial plants. We recommend the close monitoring of the fate of the surviving mangroves and the likely transformation of such into completely terrestrial ecosystems. We likewise recommend the close monitoring of the coastal fisheries as may be linked to such post-quake loss of intertidal habitats, and carefully design management measures to mitigate such impact. © 2015 Elsevier Ltd.